2020
DOI: 10.1111/jdv.16145
|View full text |Cite
|
Sign up to set email alerts
|

The Warburg effect and tumour immune microenvironment in extramammary Paget's disease: overexpression of lactate dehydrogenase A correlates with immune resistance

Abstract: Background Extramammary Paget's disease (EMPD) is a rare malignant skin cancer. One of the hallmarks of cancers, including EMPD, is an enhancement of aerobic glycolysis, which is also known as the Warburg effect. In the last step of glycolysis, the enzyme lactate dehydrogenase A (LDHA) catalyzes the conversion of pyruvate to lactic acid, the accumulation of which contributes to the creation of an acidic tumour microenvironment. This in turn results in immunosuppression in various types of cancers. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Eventually, this condition can cause immunosuppression in melanoma tumors (27). LDH-A mRNA expression was associated with an increased number of PD-L1-and PD-1-positive M2 macrophages in the tumor microenvironment of patients with extramammary Paget disease (28). A preclinical study revealed that the stimulation of melanoma cells with lactate upregulated the expression of PD-L1 and altered immunomodulation in the tumor microenvironment; also, blockade of LDH-A could improve the efficacy of anti-PD-1 treatment (27).…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, this condition can cause immunosuppression in melanoma tumors (27). LDH-A mRNA expression was associated with an increased number of PD-L1-and PD-1-positive M2 macrophages in the tumor microenvironment of patients with extramammary Paget disease (28). A preclinical study revealed that the stimulation of melanoma cells with lactate upregulated the expression of PD-L1 and altered immunomodulation in the tumor microenvironment; also, blockade of LDH-A could improve the efficacy of anti-PD-1 treatment (27).…”
Section: Discussionmentioning
confidence: 99%
“…On the conditions of hypoxia, cancer cells exhibit adaptive metabolic changes. These include conversion of glucose to lactic acid and increased glucose uptake through promotive glucose transporters (GLUTs), a phenomenon known as the Warburg effect [26]. Last, but not the least, Nutrition is another factor leading to the development of disease [27].…”
Section: Discussionmentioning
confidence: 99%
“…On the conditions of hypoxia, cancer cells exhibit adaptive metabolic changes. These include the conversion of glucose to lactic acid and increased glucose uptake through promotive glucose transporters (GLUTs), which is a phenomenon also known as the Warburg effect [22].Finally, nutrition is another factor contributing to the development of disease [23].…”
Section: Discussionmentioning
confidence: 99%